The Time Variation of Liquidity Risk on US Stock Markets - Michael Ludwig (Credit and Capital Markets – Kredit und Kapital, 2018)
The influence of liquidity costs and liquidity risk on asset returns has been proven by several empirical studies. This paper analyzes the conditional version of the liquidity-adjusted capital asset pricing model and shows that betas significantly vary over different economic regimes and that liquid portfolios provide diversification benefits compared with illiquid portfolios. The results support the effects of a flight-to-liquidity. The time variation of liquidity betas induces additional risk for investors, which has important implications for investment decisions and asset allocation. – – Die Zeitschwankung des Liquiditätsrisikos in US-Aktienmärkten Der Einfluss von Liquiditätskosten und Liquiditätsrisiko auf die Renditen verschiedener Assets wurde bereits durch einige Studien belegt. Dieses Paper untersucht das conditional liquidity-adjusted capital asset pricing model und zeigt, dass die Liquidity-Betas signifikant über verschiedene Marktphasen hinweg schwanken und dass liquide Portfolios Diversifikationsvorteile gegenüber illiquiden Portfolios bieten. Die Ergebnisse unterstützen den Flight-to-Liquidity-Effekt. Die Schwankungen der Liquidity-Betas erzeugen zusätzliche Risiken für Investoren, die bei Investmententscheidungen und der Portfoliostrukturierung berücksichtigt werden müssen.
Keywords: G11; G1; 330; CAPM; liquidity risk; regime switching model; time variation; liquidity betas